Une institution en formation : la police ottomane à l’époque d’Abdülhamid II - Noémi Lévy (European Journal of Turkish Studies)
Officially created in 1845, the Ottoman police was an institution in the process of formation until the end of the 19th century. I focus here on the Hamidian regime (1876-1909), examining how this institution was created and how it was integrated into Ottoman urban society. The point is to understand how the police became an essential and legitimate actor in the enforcement of public order in both the Ottoman Empire and, later, the Republic of Turkey. The article further examines how the police managed their integration into the “field” of the city and developed their priorities and their relationships with urban people. The article suggests that the traditional vision of a police institution as only concerned with the interests of the sultan should be revised, and identifies some dynamics that continued under successive regimes.